In-orbit operation and performance of the CubeSat Soft X-ray polarimeter PolarLight. Issue 1 (1st January 2021) - Li, Hong; Long, Xiangyun; Feng, Hua; Wu, Qiong; Huang, Jiahui; Jiang, Weichun; Minuti, Massimo; Yang, Dongxin; Citraro, Saverio; Nasimi, Hikmat; Yu, Jiandong; Jin, Ge; et al.
Abstract: PolarLight is a compact soft X-ray polarimeter onboard a CubeSat, which was launched into a low-Earth orbit on October 29, 2018. In March 2019, PolarLight started full operation, and since then, regular observations with the Crab nebula, Sco X-1, and background regions have been conducted. Here we report the operation, calibration, and performance of PolarLight in the orbit. Based on these, we discuss how one can run a low-cost, shared CubeSat for space astronomy, and how CubeSats can play a role in modern space astronomy for technical demonstration, science observations, and student training.